Heat and Mass Balances in Liquid Soap Production for Sustainable Industrial Development Aligned with SDGs - Puspita Nurlilasari; Tiara Maylafaizah Br Bangun; Maelani Sri Agustine (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study presents a comprehensive analysis of mass and energy balances in the liquid soap manufacturing process with the objective of enhancing process efficiency and promoting cleaner production principles in alignment with the United Nations Sustainable Development Goals (SDGs), particularly SDG 9 (Industry, Innovation and Infrastructure), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). Leveraging data compiled from over 60 international journal publications and validated through process simulation software (Aspen Plus®), the research systematically quantifies the flow of materials and energy within each stage of the production process. The investigation identifies critical inefficiencies such as excessive energy consumption in drying and waste sludge generation. Through scenario analyses including feedstock substitution with waste cooking oil and heat integration techniques, the study demonstrates potential reductions in raw material costs by up to 18%, energy consumption by 10%, and greenhouse gas emissions by approximately 28%. These findings underscore the significant role of integrated mass and energy management strategies in steering traditional manufacturing towards sustainable, economically viable, and environmentally responsible operations.